(untitled) (Phenomenology, Humanities and Sciences, 2024)
The facilitation of teaching, rather than traditional education, enables the student to be more skillful and adaptable to the changes that practical situations present, as knowledge itself is changeable. The training of psychologists includes the development of skills and competencies that underpin their professional identity, such as clinical psychological listening. This article aims to discuss the possibilities of developing clinical listening from a theoretical discipline in undergraduate psychology. The theoretical foundation was the active methodologies and the proposal of Carl Rogers’ student-centered teaching. The method used was of a qualitative nature, of phenomenological inspiration. The analysis generated two categories, namely: the bond and facilitating attitudes in the teacher-student relationship; active methodologies, the training process and the development of listening skills. It is understood that the affective quality of the relationship between the students and the teacher during the discipline, added to the active methodologies employed in the development of the evaluative and classroom activities, enabled significant learning consistent with the learning objective. It is suggested that more research encompassing listening practices in psychology be carried out.